The Comparation of Students’ Reading and Critical Reading Competency in Junior High School - Chrispayana, I Putu Marten (Universitas Pendidikan Ganesha, 2020)
The students’ critical reading could be beneficial towards their reading competency. The present research was aspired to describe and compare the students’ reading competencies and students; critical reading. The students’ critical reading was laid on high-order-reading items across classes, text genres, and reading indicators. The design implemented was a descriptive and comparative research. The sample size of this research consisted of 121 student’s altogether. The instrument used to collect data was that of a Reading Competency Test. The analysis techniques implemented in the research were Measures of Central Tendency and Simultaneous Comparison. The result of the analysis shows the students’ reading competency mean score = 35.02 out of the total reading competency score = 100. The range on the reading competency is equal to 60.00. Therefore, the students’ reading competency variability is very large (variance = 0.67). The analysis shows the simultaneous F test is 0.084. The significant score of 0.97 is higher than 0.05 which interpreted as if there is no significant difference between every class scores in term of answering reading test with higher order reading items. The score of reading competency implies that EFL teachers need to train their students intensively and extensively in reading processes to enhance their ability in determining the main ideas, specific ideas, textual references, and word and phrase meanings of both the descriptive and recount texts